Subcutaneous Emphysema, Pneumothorax, Pneumomediastinum, and Pneumoperitoneum During Colonoscopic Balloon Dilation: A Case Report - Yi-Chen Chan; Yu-Chuan Tsai; Shih-Yuan Fang (Kaohsiung Journal of Medical Sciences, 2010)
A 77-year-old woman underwent colonoscopic balloon dilatation for colonic stricture 1 year after laparoscopic anterior resection of sigmoid colon cancer. During the balloon dilatation, panfacial swelling and apnea were noted. Emergency endotracheal intubation was undertaken. Chest X-ray revealed diffuse subcutaneous emphysema and bilateral pneumothorax. We discuss the possible mechanism and management of this uncommon complication during therapeutic colonoscopy.